Efektivitas Peraturan Daerah Provinsi Jawa Barat Nomor 9 Tahun 2014 Tentang Penyelenggaraan Pembangunan Ketahanan Keluarga dalam Upaya Menekan Angka Perceraian di Jawa Barat - Rinrin Warisni Pribadi (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2021)
Abstract: Regional Regulation (Perda) on the Implementation of Family Resilience Development in 2014 aims to minimize various family problems that require the role of the government and the wider community. These problems include: the high divorce rate, the number of cases of domestic violence and the presence of family heads who do not have a permanent job. Under these circumstances, it is necessary to have rules that can protect the family from things that disturb the integrity of the family. This research study reveals the effectiveness of Perda No. 9/2014 on the phenomenon of the sharp increase in divorce cases from the 2018-2020 period, to what extent the role of the government in anticipating the factors that cause divorce in society. Researchers conducted research using literature review methods